Alternative Properties in Liquid Fuels and Blends - Romano, Silvia Daniela (2022)
This work summarises the results of the research program at the Renewable Energy Group (GER) of the University of Buenos Aires on alternative properties for the characterization of liquid fuels. The study included fossil fuels: diesel fuel, gasoline, and methanol, and biofuels: biodiesel from different feedstocks and bioethanol. Blends of diesel fuel/biodiesel, gasoline/bioethanol, gasoline/methanol, biodiesel/butanol, and diesel fuel/biodiesel/butanol were also studied. The electrical, acoustical, and optical properties of fuels and blends were determined as a function of temperature and composition. From these results, the composition of blends was accurately estimated from measurements of permittivity and temperature. The research program included the study of correlations of the alternative properties with those indicated in the international quality standards for liquid fuels (kinematic viscosity, methanol content, flash point). These correlations make possible to verify the quality of liquid fuels with simpler and more convenient measurements in industrial settings, and also in the laboratory.